Central banks as agents of economic development - Gerald Epstein (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
In the last two decades, there has been a global sea change in the theory and practice of central banking. The currently dominant `best practice' approach to central banking consists of the following: (1) central bank independence (2) a focus on inflation fighting (including adopting formal `inflation targeting') and (3) the use of indirect methods of monetary policy (that is, short-term interest rates as opposed to direct methods such as credit ceilings). This paper argues that this neo-liberal approach to central banking is highly idiosyncratic in that, as a package, it is dramatically different from the historically dominant theory and practice of central banking, not only in the developing world, but, notably, in the now developed countries themselves. Throughout the early and recent history of central banking in the US, England, Europe, and elsewhere, financing governments, managing exchange rates, and supporting economic sectors by using `direct methods' of intervention have been among the most important tasks of central banking and, indeed, in many cases, were among the reasons for their existence. The neo-liberal central bank policy package, then, is drastically out of step with the history and dominant practice of central banking throughout most of its history. – financing ; institutions ; central banks ; history ; development
Keywords: E5; N2; O2; 330; Zentralbank; Geldpolitik